1999
DOI: 10.20965/jaciii.1999.p0050
|View full text |Cite
|
Sign up to set email alerts
|

Determinism Measurement in Time Series by Chaotic Approach and Its Applications

Abstract: Frequently irregular-looking time series may have a deterministic cause, which is why it is called deterministic chaos. Even if a time series has a little noise, it is not always easy to recognize noise by looking at data. Fast Fourier transform (FFT) is used to extract characteristic frequencies. A chaotic time series consists of an infinite number of frequency elements, producing a broad continuous power spectrum but has few distinguishable characteristics. We propose a way, called trajectory parallel measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…TPM, based on the algorithm proposed by Fujimoto and Iokibe [23], is used in a way similar to its use in Refs. [24,25], as follows:…”
Section: Analytical Methods Based On the Nonlinear Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPM, based on the algorithm proposed by Fujimoto and Iokibe [23], is used in a way similar to its use in Refs. [24,25], as follows:…”
Section: Analytical Methods Based On the Nonlinear Dynamicsmentioning
confidence: 99%
“…4. As was the case in previous studies in which Γ was determined [23], the asymptotic value of the slope as shown in Fig. 3 is used to determine Γ .…”
Section: Orbital Instabilitymentioning
confidence: 99%
“…Con base en estudios anteriores (Takens, 1981) se puede asumir que el ruido de fondo está conformado por elementos no determinísticos, mientras que las señales producidas por la fuga del gas a alta presión contienen componentes determinísticas. Con el fin de discriminar entre los dos tipos de señales adquiridas, se usa el método TPM (por las siglas de trajectory parallel measure) (Fujimoto & Lokibe, 1999), con el cual se puede determinar la presencia de fuga comparando con un valor umbral fijado.…”
Section: Teoría Del Caosunclassified